2022
DOI: 10.1093/tropej/fmac088
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interpregnancy intervals on perinatal and neonatal outcomes in a multiethnic Pakistani population

Abstract: Background Short birth intervals (SBIs) and long birth intervals (LBIs) have been shown to have serious implications for health of both mothers and their children. This study was aimed to investigate the determinants and reproductive outcome of SBI and LBI in a multiethnic Pakistani population. Methods In a cross-sectional prospective study design, 2798 women admitted in a tertiary-care hospital in Islamabad for delivery were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The remaining studies were conducted in Bangladesh (n = 3) [ 45 , 50 , 54 ], Japan (n = 4) [ 47 , 75 77 ], Australia (n = 3) [ 43 , 56 , 78 ], Afghanistan (n = 2) [ 53 , 79 ], Indonesia (n = 1) [ 44 ], Nepal (n = 1) [ 80 ], and Papua New Guinea (n = 1) [ 81 ]. More than half of the included studies were cross-sectional (n = 23)[ 38 40 , 42 45 , 48 50 , 52 , 53 , 55 , 61 , 63 , 64 , 68 , 70 , 71 , 79 , 82 – 84 ], one quarter (n = 12)[ 41 , 47 , 51 , 54 , 66 , 67 , 73 , 75 , 78 , 85 87 ] were cohort studies, and the remaining six studies were case controls [ 46 , 62 , 72 , 74 , 81 , 88 ]. Twenty-five studies were facility-based [ 41 – 44 ,…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies were conducted in Bangladesh (n = 3) [ 45 , 50 , 54 ], Japan (n = 4) [ 47 , 75 77 ], Australia (n = 3) [ 43 , 56 , 78 ], Afghanistan (n = 2) [ 53 , 79 ], Indonesia (n = 1) [ 44 ], Nepal (n = 1) [ 80 ], and Papua New Guinea (n = 1) [ 81 ]. More than half of the included studies were cross-sectional (n = 23)[ 38 40 , 42 45 , 48 50 , 52 , 53 , 55 , 61 , 63 , 64 , 68 , 70 , 71 , 79 , 82 – 84 ], one quarter (n = 12)[ 41 , 47 , 51 , 54 , 66 , 67 , 73 , 75 , 78 , 85 87 ] were cohort studies, and the remaining six studies were case controls [ 46 , 62 , 72 , 74 , 81 , 88 ]. Twenty-five studies were facility-based [ 41 – 44 ,…”
Section: Resultsmentioning
confidence: 99%
“…Socio-demographic and economic factors, women's reproductive history, and child-related factors were commonly investigated in relation to short birth interval. Mother's educational status showed varying associations with short birth interval across different studies, with some reporting increased risks among illiterate mothers [78] and others reporting decreased odds among women with higher education [29]. Although educated women usually tend to delay their first pregnancy [89], it has also been hypothesised that these women may want to compress motherhood into fewer years and, therefore are likely to have shorter birth intervals [97].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age was one of the most investigated demographic factors in relation to short birth interval. Out of the 11 studies that investigated maternal age, four reported a positive association between maternal age and short birth interval, four reported a negative association, and three found no significant association [50,54,78]. Although measured slightly differently across the studies, the findings were inconsistent, with varying risks observed across different age groups.…”
Section: Predictors Of Short Birth Intervalmentioning
confidence: 99%
See 2 more Smart Citations